Cervical cancer screening utilization among HIV-positive women in Edo State, Nigeria - Ngozi R. Osunde; Mercy N. Anayo; Ona Patience; Favour E. Omoregie (MGM Journal of Medical Sciences)
Background: The enhanced risk of cervical cancer among women with human immunodeficiency virus (HIV) stems from the close association between HIV and increased rates of persistent human papillomavirus (HPV) infection. Detecting pre-malignant lesions early through screening is crucial, as cervical cancer is preventable. Identifying these lesions promptly could potentially save many women’s lives. Objective: This study aimed to assess the utilization of cervical screening services among women attending an HIV clinic in Edo State, Nigeria. Specific objectives included examining awareness levels, utilization rates, and potential barriers to access. Materials and Methods: This cross-sectional study was conducted at an institution and involved HIV-positive women attending an HIV clinic from August 2022 to July 2023. The study utilized a convenience sampling method with a sample size of 370 participants. Data reliability, deemed adequate at 0.781, was data reliability of 0.781 obtained was adequate for the study utilized. Analysis was performed, and findings were presented using frequency tables. Hypotheses were tested using χ2 at a significance level of 0.05. Results: The participants’ mean age was 38.25 ± 4.51 years, with an average age at menarche of 15.12 ± 3.56 years, age at first intercourse at 18.21 ± 3.41 years, and years of HIV status at 7.11 ± 2.12 years. The mean duration of antiretroviral therapy (ART) was 6.72 ± 5.21 years. One hundred ninety-one individuals (51.6%) reported awareness of screening, while 65 (17.6%) had undergone screening. There was a significant association between awareness of screening and its utilization. (P < 0.001 removed). Among the 305 participants who had not undergone screening, 261 (85.6%) expressed willingness to do so. Barriers to cervical cancer screening included fear of the results (257 participants, 84.3%), financial constraints (200 participants, 65.6%), absence of symptoms (240 participants, 78.3%), and lack of motivation (289 participants, 94.8%). Conclusion: The study findings indicated insufficient awareness among participants and low utilization of screening services. As a result, it is recommended that enhancing healthcare workers’ abilities to promote cervical cancer awareness and encourage adherence to screening within this population is crucial to boost uptake.